Training of Shibori techniques for Women's Group in Family Welfare Programme in Kedungkandang, Malang - Aryntika Cahyantini; Fatmasari Endayani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Improving the family economy for the PKK group in Sawojajar Village, Kedungkandang District, Malang City is an effort to empower families. Improving skills by utilizing and developing existing potential aims to increase family income. Shibori is one of the arts from Japan, starting to be widely known and in demand in Indonesia. Shibori making, by making a pattern on a cloth is created through the process of immersing it in dyes. The purpose of this service is to develop Shibori cloth crafts and to develop marketing through digital marketing so that have better economic value. This community service program uses methods in the form of training and demonstrations, namely demonstration and demonstration of certain processes, conditions, and conditions that are being carried out to provide learning or understanding to participants. The training on making Shibori batik consists of a preparation stage, a training implementation stage, and an evaluation of the process and results. The training received a positive response from partners participating in these activities. The results of the training are increased knowledge and new insights for partners and their creativity. This is evidenced by the formation of various types of batik motifs and knowledge of digital marketing, and sales increased by 100% in 4 months with the establishment of a marketing system through social media and marketplaces so that partners can experience an increase in economic terms.